The symbolic meaning of the Wura Bungi Monca dance movements in Maria Village, Bima Regency - Ani Nur Auliyatun Latifah; Lesa Paranti (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Wura Bongi Monca is a traditional welcoming dance of the Bima community that has undergone a transformation from the royal court dance of the Mbojo Sultanate into a contemporary creative dance performed in various cultural institutions, including Sanggar La Diha in Maria Village, Bima Regency. Despite its evolution, the symbolic representations and cultural meanings embedded within its choreographic structure remain underexplored within the sociocultural context of the local community. This study aims to examine the semiotic dimensions of the Wura Bongi Monca dance movements as performed in Sanggar La Diha elucidating their symbolic and cultural significance in the collective identity of the Maria Village community. Employing a qualitative research methodology with a semiotic approach. Semiotics is used in this research to explore and interpret symbols and meanings in the Wura Bongi Monca dance movements. This study integrates data collected through participant observation, in-depth interviews, and documentary analysis. The research informants include choreographers from the Mbojo Sultanate and Sanggar La Diha, historians, cultural experts, traditional leaders, dancers, and community members. The findings indicate that Wura Bongi Monca plays a pivotal role in the sociocultural fabric of Maria Village. This dance serving both ceremonial and entertainment functions. The choreographic consists of distinct symbolic movements, including paleo, palika, lele, foka, horma, and mangko, which are emblematic of Bima’s traditional dance heritage. The semiotic analysis reveals that these movements convey profound meanings: rai lu’u symbolizes the reception of blessings, lele represents resilience, sangge’de mangko signifies strength, paleo reflects consciousness, foka denotes openness, horma expresses supplication, wura bongi and kakiri kamai signify hospitality, kidi boko embodies power, and lampa palika-losa represents courtesy.   Tari Wura Bongi Monca merupakan tari penyambutan tamu khas masyarakat Bima yang mengalami transformasi dari Tari Istana Kesultanan Mbojo menjadi tari kreasi baru yang berkembang di berbagai sanggar, termasuk Sanggar La Diha di Desa Maria, Kabupaten Bima. Meski telah mengalami modifikasi, simbol dan makna yang terkandung dalam gerak tari ini belum banyak dikaji secara mendalam dalam konteks budaya masyarakat setempat. Tujuan penelitian ini adalah untuk menganalisis gerak Tari Wura Bongi Monca di Sanggar La Diha yang sarat akan simbol dan makna kehidupan masyarakat Desa Maria. Metode penelitian menggunakan metode kualitatif dengan pendekatan semiotika. Semiotika digunakan dalam penelitian ini untuk menelusuri dan menginterpretasikan simbol serta makna pada gerak Tari Wura Bongi Monca. Teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Narasumber penelitian ini adalah koreografer dari Kesultanan Mbojo dan Sanggar La Diha, sejarawan, budayawan, pemangku adat, penari, serta masyarakat Desa Maria. Hasil penelitian menunjukkan Tari Wura Bongi Monca berperan penting dalam kehidupan sosial budaya masyarakat Desa Mari. Tarian ini digelar untuk penyambutan tamu dan hiburan masyarakat Desa Maria. Simbol gerak Tari Wura Bongi Monca yaitu, paleo, palika, lele, foka, horma, dan mangko. Gerak tersebut yang menjadi ciri khas gerak tari di tanah Bima. Makna gerak Tari Wura Bongi Monca yaitu, rai lu’u bermakna menjemput berkah, lele bermakna ketegaran, sangge’de mangko bermakna kekuatan, paleo bermakna kesadaran, foka bermakna keterbukaan, horma bermakna permohonan, wura bongi dan kakiri kamai bermakna selamat datang, kidi boko bermakna kekuatan, dan lampa palika-losa bermakna kesopanan.